2015
DOI: 10.4314/ajtcam.v12i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect and GC-MS analysis of traditionally used <i>Boswellia sacra</i> oleo gum resin (Frankincense) extract in

Abstract: Background: The water extract of oleo-gum-resin of Boswellia sacra Fleuckiger (Burseraceae) is used in the treatment of liver problems in the Middle East and Arab-African countries. The present study was carried out to evaluate its effect on liver injury induced by carbon tetrachloride in acute and chronic liver injury models. Materials and Methods:The Boswellia sacra extract was administered at doses of 2 ml/kg and 5 ml/kg. Silymarin, a known hepato-protective agent was used as standard. The extract was subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…B. sacra oleo gum resin is used in the treatment of gastric and hepatic disorders [14], skin disorders [15], for its hepatoprotective activity [16], analgesic effect [4], antiglycation and antioxidant activities [17], tumor suppression [18], anticoagulation effects [19], antinflammatory activity [20], and cardioprotective effects [21].…”
Section: Introductionmentioning
confidence: 99%
“…B. sacra oleo gum resin is used in the treatment of gastric and hepatic disorders [14], skin disorders [15], for its hepatoprotective activity [16], analgesic effect [4], antiglycation and antioxidant activities [17], tumor suppression [18], anticoagulation effects [19], antinflammatory activity [20], and cardioprotective effects [21].…”
Section: Introductionmentioning
confidence: 99%
“…Drug hepatotoxicity, is the leading cause of acute liver failure in the clinic worldwide [60]. Boswellia sacra extract shown to be hepatoprotective agent [61] however, FEO has not yet been reported for hepatoprotection effect. Acetaminophen is a classical hepatotoxin that is responsible for almost 50% of all acute liver failure cases in the USA, the UK and many Western countries [60].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the extract though administered at high doses did not significantly affect the levels of liver biomarkers in serum and histological examination also did not show any distinct damage to the organ. We had earlier reported that water extract of Boswellia sacra that is free of boswellic acids showed hepatoprotective effect against carbon tetrachloride induced hapatotoxicity in rats (Asad and Alhumoud, 2015). We attributed this effect to the antioxidants present in the extract that included carvacol, cineole, linalool and furanmethanol, which were shown to be present in the extract.…”
Section: Discussionmentioning
confidence: 99%